Waveguide Bragg Gratings in Ormocer®s for Temperature Sensing - Girschikofsky, Maiko Girschikofsky; Rosenberger, Manuel; Förthner, Michael; Rommel, Mathias; Frey, Lothar; Hellmann, Ralf (Sensors, 2017)
Embedded channel waveguide Bragg gratings are fabricated in the Ormocer® hybrid polymers OrmoComp®, OrmoCore, and OrmoClad by employing a single writing step technique based on phase mask technology and KrF excimer laser irradiation. All waveguide Bragg gratings exhibit well-defined reflection peaks within the telecom wavelengths range with peak heights of up to 35 dB and –3 dB-bandwidths of down to 95 pm. Furthermore, the dependency of the fabricated embedded channel waveguide Bragg gratings on changes of the temperature and relative humidity are investigated. Here, we found that the Bragg grating in OrmoComp® is significantly influenced by humidity variations, while the Bragg gratings in OrmoCore and OrmoClad exhibit linear and considerably high temperature sensitivities of up to –250pm/°C and a linear dependency on the relative humidity in the range of –9 pm/%. © 2017 by the authors. Licensee MDPI, Basel, Switzerlan
Keywords: Bragg grating; Humidity; Hybrid polymer; Ormocer®; Temperature